Answer:
length of each edge = (x + 3)
Explanation:
The surface area of each face of the cube = (
+ 6x + 9)
. But the surface of a cube has the shape of a square. So that,
Area of a square = length x length
=
![l^(2)](https://img.qammunity.org/2022/formulas/mathematics/high-school/d32brpjoz8c32mbvrse5ikpwt182uol8s9.png)
By factorizing the area,
+ 6x + 9 =
+ 3x + 3x + 9
= (
+ 3x) (3x + 9)
= x(x +3) + 3(x + 3)
= (x + 3)(x + 3)
=
![(x + 3)^(2)](https://img.qammunity.org/2022/formulas/mathematics/high-school/t2oto56g2pa2q84rt6254e0cuq6nkuxe8o.png)
+ 6x + 9 =
![(x + 3)^(2)](https://img.qammunity.org/2022/formulas/mathematics/high-school/t2oto56g2pa2q84rt6254e0cuq6nkuxe8o.png)
Thus,
=
![l^(2)](https://img.qammunity.org/2022/formulas/mathematics/high-school/d32brpjoz8c32mbvrse5ikpwt182uol8s9.png)
find the square root of both sides
l = (x + 3)
length of each edge = (x + 3)